PENGARUH KOMPETENSI GURU, INSENTIF DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA GURU SMA NEGERI 1 PATIMUAN KABUPATEN CILACAP - Setyono, Hendro; Sudjadi, Achmad (Sainteks, 2011)
This study entitled “ Effect of Teachers competence, Incentives and The Performance of Physical Work Environment Teacher SMA Negeri 1 Patimuan Cilacap District." The purpose of this study to determine and analyze the influence of teacher competence, incentives, and physical work environment to increase teacher performance and to investigate and analyze the influence of teacher competence, incentives and physical work environment factors that give the most dominant influence on improving the performance of SMA Negeri 1 teacher Patimuan Cilacap District. Target of this research is teacher SMA Negeri 1 Patimuan Cilacap District. The study was conducted in SMA Negeri 1 Patimuan Cilacap District held in September of 2009. This research study is a survey that took the case on teacher performance SMA Negeri 1 Patimuan Cilacap District. The population in this study are all teachers SMA Negeri 1 Patimuan Cilacap District teachers numbering 31 people. The samples in this study was to use saturated sampling method. The analytical tool used in this study is multiple regression analysis, whereas to test levels of significance using the F test and t test Results of multiple regression analysis equation: Y = -3.150 + 0.170 X1 + 0.416 X2 + 0.291 X3 Coefficient of determination (R2) of 0.774 or 77.40 percent of the mean variation of teacher competence variable, the incentives and physical work environment can explain the performance of high school teachers SMA Negeri 1 Patimuan Cilacap Regency at 77.40 percent, while 22.60 percent is a variation of the variable other outside variables such as motivation, skills, attitude, work ethic, and ability to work. The conclusion of this study is that the first teacher competence has a positive impact on teacher performance. Both incentives have a positive impact on teacher performance. Third physical working environment of teachers have a positive impact on teacher performance. The four competencies of teachers, incentives and physical working environment of teachers jointly have a positive impact on teacher performance. Fifth teacher competence is a factor that has the most impact on teacher performance SMA Negeri 1 Patimuan Cilacap District. Keywords: Teachers, Incentives, Work Environment and Physical Performance Teachers